PRODUKSI ENZIM XYLANASE MELALUI SELEKTIFITAS MOISTENING AGENT SECARA FERMENTASI - S.P. Abrina Anggraini; Fenni Suryanti (BUANA SAINS, 2008)
The environmental pollution is serious problems in the pulp and paper industry especially in lignin degradation process. Recently conventional bleaching process used toxic chemicals such as chlorine that is harm full for the environment. Therefore, an alternative technology, i.e enzyme technology that can reduce chlorine using is required. The goal of this project was to produce the best xylanase activity from Aspergillus niger using solid state fermentation method with wheat bran substrate in which several kind of moistening agent (MA) was selected and the effect of enzyme abilities to degradation hemicelluloses. The experimental result showed that the best xylanase activity was produced using wheat bran : MA ratio (w/v) 1:2, that is 3,1703 IU/ml and cellulase was found to be 1,5299 IU/ml after 4 days incubation with MA nitrogen organic salt solution. With the same variable, addition additive xylose give xylanase activity to be 3,856 IU/ml and cellulase is 1,614 IU/ml